THE IMPORTANCE OF FORENSICS IN CRIMINAL PROCEEDINGS - Makhambetova , Айгүл Көбейсінқызы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
This article discusses the importance of forensics in criminal proceedings. On the basis of analysis, along with the importance of the criminal process author reveals the lawsuit.